THE ROLE OF COMPUTATIONAL THINKING AND CODING IN MATHEMATICS EDUCATION: BRIDGING MATHEMATICS WITH MODERN TECHNOLOGICAL APPLICATIONS (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
The combination of computational thinking and coding with mathematics education has become a revolutionary way to equip students to live in a technologically developed world. The paper will discuss the importance of computational thinking and coding in improving mathematical knowledge, problem-solving abilities, and interest in using modern technological applications. The paper will look at how these two disciplines interact to overcome the academic and political hurdles that have impeded integration such as curriculum restrictions, teacher readiness, and policy opposition. The study aims to uncover the connection between computational thinking and the development of more profound mathematical reasoning and the connection of theoretical mathematics with practical applications using a mixed-methods design that includes the use of surveys, interviews, and classroom observations. The results indicate that coding is a versatile tool that can be used in visualizing abstract ideas, facilitate the learning across disciplines, and close the equity gap in access to technology education. The article ends by providing suggestions on how the curriculum should be reformed, how teachers should be trained, and what policy advocacy needs to be done to help these skills be integrated smoothly in mathematics education.